Motivasi Kerja Pramusaji pada HQ Restaurant di Hotel Truntum Kuta, Bali - I Nyoman Arcana; Luh Octa Lestari Dewi; Luh Mira Astuti Pranadewi; Ni Putu Ariesta Budiani (HeadWay Research & Developemnt, 2026)
Employee motivation is a critical factor influencing service quality in the hospitality industry, particularly among frontline employees who interact directly with guests. Despite its importance, limited research has specifically examined the work motivation of restaurant waitresses in individual hotel restaurants in Indonesia. This study aims to analyze the work motivation of waitresses at HQ Restaurant, Hotel Truntum Kuta, Bali, based on Herzberg’s Two-Factor Theory. A quantitative descriptive approach was employed using a census sampling technique involving all eight waitresses working at the restaurant. Primary data were collected through a structured questionnaire consisting of 20 statements measured on a five-point Likert scale. The data were analyzed descriptively by calculating the mean score for each motivation indicator. The results indicate that the overall work motivation of the waitresses is relatively high, with an overall mean score of 3.49. The highest scores were obtained for the work itself (3.81), company policy and administration (3.68), interpersonal relationships (3.68), responsibility (3.62), and salary (3.49). In contrast, working conditions (3.24), quality of supervision (3.37), achievement (3.25), and recognition (3.24) received comparatively lower evaluations. The findings support Herzberg’s theory, suggesting that while hygiene factors reduce job dissatisfaction, intrinsic motivational factors play a more significant role in sustaining employee motivation. The study recommends improving employee recognition, supervisory practices, and working conditions to enhance motivation and service quality.